Basic researchOccurrence of large-scale mitochondrial DNA deletions in human colorectal cancer - Akouchekian, Mansoureh; Houshmand, Massoud; Hemati, Simin; Shafa, Mehdi (Archives of Medical Science, 2008)
Introduction: The aim of this study was to determine the mutation patterns of colon cancers through screening of different regions of mitochondrial DNA (mtDNA) in colon cancer patients. Material and methods: In order to investigate whether deletions exist in the mitochondrial DNA of colon cancer patients, we used a PCR assay to assess the presence of large-scale deletions. We screened four regions of the mitochondrial genome by PCR amplification and Southern blot analysis followed by DNA sequencing. Previously, deficiency in mitochondrial complex I has been reported; therefore we focused on the region of mtDNA that encodes the genes of this complex. Results: In 11 out of 90 patients, we found an 8.7 kb deletion. Large-scale deletions of mtDNA are common events that have been found to occur in human ageing and in patients with mitochondrial myopathies. Based on our results the mtDNA 8.7 kb deletion occurs in 12.2% of the colorectal cancer (CRC) samples. Conclusions: As reactive oxygen species (ROS) are continuously generated by the respiratory chain, they may cause significant oxidative damage to mtDNA (for example mtDNA deletions or mutations) if not efficiently eliminated. Defective respiratory enzymes containing protein subunits encoded by the deleted mtDNA may further enhance free radical production, resulting in more profound oxidative damage in CRC patients.